Understanding the Structural Elasticity of RNA and DNA: All‐Atom Molecular Dynamics (Adv. Theory Simul. 1/2023). Issue 1 (10th January 2023) - Zhang, Yingtong; Yan, Miao; Huang, Tingting; Wang, Xianghong
Abstract : All‐Atom Molecular Dynamics Helical acids play important roles in many biological processions. In the research article 2200534, Zhang, Yan and coworkers analyse the structural elasticity and microscopic configurations of dsDNA and dsRNA in sodium solution.